Chemistry and Hypoglycemic Activity of GPR119 Agonist ZB-16 - Tyurenkov, Ivan N.; Kurkin, Denis V.; Bakulin, Dmitry A.; Volotova, Elena V.; Morkovin, Evgeny I.; Chafeev, Mikhail A.; Karapetian, Ruben N. (Frontiers in Endocrinology, 2018)
This article is to highlight the chemical properties and primary pharmacology of novel GPR119 agonist ZB-16 and its analogues, which were rejected during the screening. Experiments were performed in vitro (specific activity, metabolism and cell toxicity) and in vivo (hypoglycemic activity and pharmacokinetics). ZB-16 exhibits nanomolar activity (EC50 = 7.3-9.7 nM) on target receptor GPR119 in vitro associated with hypoglycemic activity in vivo. In animals with streptozotocin-nicotinamide induced type 2 diabetes mellitus (STZ-NA T2D) daily oral dose of ZB-16 (1 mg/kg) or sitagliptin (10 mg/kg) for 28 days resulted in the reduction of blood glucose levels. The effects of ZB-16 were comparable to the hypoglycemic action of sitagliptin. ZB-16 demonstrated relatively low plasma exposition, high distribution volume, mild clearance and a prolonged half-life (more than 12 hours). The present study demonstrates that the targeted search for selective GPR119 receptor agonists is a well-founded approach for developing novel drugs for the therapy of T2D. Based on the combination of high in vitro activity (compared to competitor standards), a useful ADME profile, distinct hypoglycemic activity comparable to the hypoglycemic activity of sitagliptin in an experimental T2D and the resulting acceptable pharmacokinetic profile, we recommend the ZB-16 compound for further research.